Surgical outcome of intradural extramedullary meningiomas without dural resection – A study on 75 cases - Roy, Kaushik; Ghosh, Partha; Saha, Suniti Kumar; Tripathy, Parimal (Asian Journal of Medical Sciences, 2019)
Background: Spinal tumor is a common cause of morbidity in otherwise healthy population, timely diagnosis and treatment of spinal tumor gives excellent outcome. Aims and Objective: We report experience and clinical outcomes of 75 cases with Intradural extramedullary meningiomas operated in last 21 years. Materials and Methods: All the patients were clinically assessed with Nurick’s Grading (both pre and post operatively). MRI was the main armamentarium for operating planning. In all the patients dural attachments were coagulated without any dural excision. Results: Out of 75 patients, 65% were female. Peak incidence was noted in 4th & 5th decade and majority of patients having tumor in the thoracic spine and lateral to the cord. The entire patient showed remarkable clinical improvement according to Nurick’s grade. Total removal was achieved in 69 (90.2%) patients. Two patients had re-growth of tumor in 1 yr. follow up. No postoperative mortality noted in the present series. Conclusion: Spinal meningioma excision without dural resection did not show any increase in recurrences.